1997
DOI: 10.1095/biolreprod56.6.1450
|View full text |Cite
|
Sign up to set email alerts
|

A Tyrosine-Phosphorylated 55-Kilodalton Motility-Associated Bovine Sperm Protein is Regulated by Cyclic Adenosine 3′,5′-Monophosphates and Calcium1

Abstract: Sperm motility is regulated by protein phosphorylation. We have recently shown that a serine/threonine phosphatase system is involved in motility regulation. Two of the components of the phosphatase system, GSK-3 and PP1gamma2, are regulated by tyrosine phosphorylation. During our investigation of sperm tyrosine-phosphorylated proteins we discovered a 55-kDa protein whose tyrosine phosphorylation correlates closely to the motility state of sperm. This protein is tyrosine phosphorylated to a much higher degree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
66
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 42 publications
8
66
3
Order By: Relevance
“…2). Some specific protein targets of tyrosine phosphorylation in sperm have been suggested and phosphorylation of these proteins has been closely linked to the onset of motility in bovine sperm (Vijayaraghavan et al 1997b(Vijayaraghavan et al , 2000.…”
Section: Motilitymentioning
confidence: 99%
“…2). Some specific protein targets of tyrosine phosphorylation in sperm have been suggested and phosphorylation of these proteins has been closely linked to the onset of motility in bovine sperm (Vijayaraghavan et al 1997b(Vijayaraghavan et al , 2000.…”
Section: Motilitymentioning
confidence: 99%
“…Moreover, these authors describe the presence of both the a and b GSK3 isoforms in bovine epididymal spermatozoa (Vijayaraghavan et al , 1997 and discovered a 55 kDa protein whose tyrosine phosphorylation was closely correlated to the motility state of epididymal bovine spermatozoa and the treatment of these cells with motility activators, like isobutylmethylxanthine or 8Br-cAMP, resulted in increased tyrosine phosphorylation of this protein (Vijayaraghavan et al 1997). The same authors showed a correlation between the 55 kDa tyrosine phosphorylation motility-associated protein and the GSK3 and suggested that GSK3, which is also regulated by tyrosine phosphorylation, could be an important key underlying motility initiation in the epididymis (Vijayaraghavan et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Since the FS and ODFs taper, the flagellum is not uniform in stiffness, becoming progressively less stiff in the distal region. In addition to the mechanical role of the sheath and ODFs, it is also well documented that the sheath and ODFs are also the site of many enzymes that support metabolism and signaling in mammalian sperm (Vijayaraghavan et al, 1997;Eddy, 2007), but these functions are beyond the scope of this review. Much of the initial description of the unique ultrastructural anatomy of the mammalian sperm was first compiled by Phillips (Fawcett, 1958, 1975; Phillips, 1969, 1970;Phillips, 1972Phillips, , 1997).…”
mentioning
confidence: 99%